Moral Challenges When Suspecting Abuse and Neglect in School Children: A Mixed Method Study - M. Forsner; G. Elvhage; B. M. Ewalds-Kvist; K. Lützén (SPRINGER, 2022)
The World Health Organization (WHO), concludes that child maltreatment is a global concern calling for a multi sectoral interdisciplinary approach. School professionals, such as social workers, teachers, and health care professionals are in positions to discover and report maltreatment enabling social workers to intervene. However, a variety of reports reveal an evident gap between incidences and frequency of number of cases reported. A review of relevant research indicates that the problem of "not reporting" suggests that moral conflicts are activated in the process of decision-making. The aim was to gain a deeper understanding of school professionals' experiences of reporting suspected neglect and abuse to the Social Welfare Board. In a mixed method approach 32 school professionals, such as teachers, social workers, nurses and psychologists participated in interviews and responded to questionnaires. Findings from the qualitative content analysis were compared to the quantitative analysis in a meta-analysis. Moral conflicts occur when faced with making decisions about how to best deal with a child's situation. Thoughts about the child's best interest and relationship with his/her parents as well as the informants ' own safety, were central. The comparative meta- analysis of both data sets revealed these conflicts commence with a moral sensitivity of possible negative consequences for the child. Moral sensitivity can be viewed as a "good" personal attribute, it paradoxically might lead to moral stress despite an open ethical climate. Based on the results of this study, further research on the interpersonal aspects of dealing with moral conflicts involved in reporting suspected child abuse is indicated.